Solving problems that matter (and getting paid for it) STEM careers in social innovation and global sustainable development - Mehta, Khanjan (State College, PA Khanjan Mehta, 2015)
Solving Problems that Matter (and Getting Paid for It) stitches together a mosaic of perspectives, experiences, and actionable insights to illuminate the smorgasbord of career pathways in social innovation and global sustainable development.
This book was self-published by Khanjan Mehta -- Title page verso.
E2-1101G donated by Dr. Rizalinda L. de Leon.
Keywords: Science -- Social aspects; Sustainable development -- Vocational guidance; Technology -- Vocational guidance; Engineering -- Vocational guidance; Engineering -- Social aspects